THE INFLUENCE OF SOFTWARE QUALITY HUMAN RESOURCES INFORMATION SYSTEM AND USER PARTICIPATION TOWARD USER SATISFACTION AS SYSTEM USER - yanuar latief (Universitas Trisakti, 2012)
The research on the influence of the quality of software human resources information systems and user participation on user satisfaction in the Bureau of Human Resources Trisakti University. The research purposes (1) Identify the effect of the quality of software human resources information system for user satisfaction as users of the system, (2) Identify the effect of user participation on user satisfaction as users of the system (3) identification of the influence of the quality of software human resource information systems and participation user together to user satisfaction as users of the system. This research is descriptive and correlational research is to describe the characteristics of respondents and aims to determine the relationship between two or more variables. The research was conducted at the Bureau of Human Resources University of Trisakti by respondents as many as 32 people and using correlational and regression analyzes. The study found that the quality of the software (Xl) and user participation (X2) either individually or group have a strong influence and positive impact on user satisfaction (1J as the user s system. From this study several conclusions can be drawn as follows: (1) there is a strong and positive relationship between software quality variables (Xl) to the satisfaction of the user m with r values of 0.584, (2) there is a strong and positive relationship between the variables user participation (X2) with user satisfaction (Y) with r value of 0.721 (3) The regression model obtained is Y = -2.125 + 0.304 software quality (Xl) + 0.397 user participation (X2), (4) regression models can state that the variable quality of the software and user participation is jointly affect user satisfaction as users of the system. It is shown from ANOVA test results were obtained Fcount of 22.642 with a significance level of F = 0.000 which is much smaller than 0.05, (5) The coefficient of determination (R Square) of 0.610 implies that, 61.0% user satisfaction can be explained by a variety of software quality and variety of user participation, while the rest is explained by other factors.